Healthcare - Ab Rahman, Jamalludin; Zulkifly, Ahmad Hafiz; Che Mohamad, Che Anuar; Mohamad, Mohd Yusof; Hashi, Abdurezak Abdulahi; Mohd Arifin, Siti Roshaidai; Nik Mohamed, Mohamad Haniki; Md Tahir, Mohd Faiz; Kaderi, Mohd Arifin; Rajion, Zainul Ahmad; Draman, Samsul; Che Ahmad, Aminudin; et al. (Centre for Islamisation (CENTRIS), IIUM, 2025)
This executive summary sets out a strategic vision for healthcare in the Muslim world by 2077, integrating Islamic values with advanced technologies. It aims to present a roadmap that addresses health's physical, mental, social, and spiritual dimensions while positioning the Muslim world as a leader in health innovation and selfsufficiency rooted in Islamic principles. Health and diseases are part of Allah's tests for human beings. The concept of good health does not denote the absence of illness in totality, rather the ability to live with any circumstances in the pursuit of performing ʿibādah to Allah. This is the key to the establishment of the Islamic health framework. Islamic framework of health (ةحصلا) and wellness (ةيفاعلا) can be represented with the health dome. The base of the dome is piled upon the pillars of alMaqāṣid al-Khamsah (the five objectives of the Sharī‘ah) upholding the principles of Raḥmatan li’l-‘Ālamīn (mercy to all) with flexible (ةﻧورﻣ), robust (نﯾﺗﻣ/يوﻗ) and adaptive (فﯾﻛﺗ) characteristics. The dome starts and ends with the ultimate purpose of serving Allah (S.W.T.). It is of utmost importance to maintain the equilibrium of the three main components of health, namely the Ummah (human), environment and disease. Each of these components encompasses various aspects, in which each aspect is essential in the maintenance of health of the population. Failure or disturbance in any of these aspects and components would lead to the diminishing of health and well-being, which may lead to disastrous ends. The challenges in maintaining each of these health components will be discussed from a general perspective as well as specifically for the Muslim population before a specific discussion on the Malaysian perspective is presented. The Muslim world is facing significant healthcare challenges, including inequitable access, dependence on external systems, and the growing burden of communicable and non-communicable diseases. Social stigma, particularly regarding mental health, and insufficient investment in healthcare infrastructure further hinder progress. These issues are exacerbated by environmental degradation, political instability, and limited technological advancement.